COVID-19 Demands Theological Reflection: Buddhist, Muslim, and Christian Perspectives on the Present Pandemic - Xiong, Jianhui (International journal of practical theology, 2020)
What are some ways that people from the Buddhist, Muslim and Christian faith traditions can reflect upon the coronavirus pandemic using a theological lens? How can Buddhist, Muslim and Christian practitioners respond in practical ways to the coronavirus pandemic, utilizing resources from their faith traditions? This contribution offers reflections on the worldwide suffering and challenges that the pandemic has caused from the perspectives of Buddhist, Muslim and Christian practitioners. Each writer offers practical resources and theological reflection from their vantage point as spiritual care providers and as people of faith.